Baseline trace metals in water and sediment of the Baleh River—a tropical river in Sarawak, Malaysia - Siong, Fong Sim; Hui, Ping Chai; Lee, Nyanti; Teck, Yee Ling; Jongkar, Grinang (Springer International Publishing, 2016)
Quantitative indices are classically employed to evaluate the contamination status of metals with reference to the baseline concentrations. The baselines vary considerably across different geographical zones. It is imperative to determine the local geochemical baseline to evaluate the contamination status. No study has been done to establish the background concentrations in tropical rivers of this region. This paper reports the background concentrations of metals in water and sediment of the Baleh River, Sarawak, derived based on the statistical methods where the areas possibly disturbed are distinguished from the undisturbed area. The baseline levels of six elements in water determined were Al (0.34 mg/L), Fe (0.51 mg/L), Mn (0.12 mg/L), Cu (0.01 mg/L), Pb (0.03 mg/L), and Zn (0.05 mg/L). Arsenic and selenium were below the detection limit. For sediment, the background values were established according to statistical methods including (mean + 2σ), iterative 2σ, cumulative distribution frequency, interquartile, and calculation distribution function. The background values derived using the iterative 2σ algorithm and calculated distribution function were relatively lower. The baseline levels calculated were within the range reported in the literatures mainly from tropical and subtropical regions. The upper limits proposed for nine elements in sediment were Al (100,879 mg/kg), Cr (75.45 mg/kg), Cu (34.59 mg/kg), Fe (37,823 mg/kg), Mn (793 mg/kg), Ni (22.88 mg/kg), Pb (27.26 mg/kg), Zn (70.64 mg/kg), and Hg (0.33 mg/kg). Quantitative indices calculated suggest low risk of contamination at the Baleh River.